Spatial Analysis of Micro-Hydro Power Plant (MHPP) Potential in Existing Irrigation Canals Using GIS and Hydraulic Head Data - Rismen Sinambela; Firman’s Bramadhani; Emyr Hidayat (CV. Get Press Indonesia, 2026)
Indonesia’s rural energy crisis encourages the utilization of existing infrastructure, including technical irrigation networks, as renewable energy sources. This study evaluates the hydroelectric potential of irrigation canals by integrating geospatial analysis and secondary hydrological data to identify feasible micro-hydro power generation sites. The research was conducted along the West Tarum Main Canal managed by BBWS Citarum in West Java, covering a 45 km primary canal segment selected through purposive sampling.The methodology employed Geographic Information System (GIS) spatial analysis using National Digital Elevation Model (DEMNAS) data with an 8.25 m resolution and daily discharge records from Automated Water Level Recorders (AWLR) collected during 2020–2025. Key parameters analyzed included gross head (H_g), dependable discharge (Q₈₀), Manning’s roughness coefficient (n), and head loss.The results identified a total hydroelectric potential of 514.29 kW distributed across five priority nodes, with an average hydraulic head of 3.91 m. A strong positive correlation was found between discharge stability and power output efficiency (r = 0.892; p < 0.001). Nevertheless, sedimentation and inorganic waste remain operational challenges affecting system performance.The study concludes that irrigation infrastructure has economically feasible energy potential due to its proximity to rural load centers, averaging 306 m. These findings support community-based electrification and renewable energy development policies in Indonesia.